Rushing into Chaos: Recapitulating Arthur Danto’s Philosophical Narrative on the Path to Post-historical Art - Gherasim, Gabriel C. (AMERICANA E-journal of American Studies in Hungary, 2022)
This essay purports to recapitulate on Danto’s reflections regarding the conceptual evolution of art’s history through the technique of philosophical narrativism. Danto’s philosophical narrative on the post-1300 meaningful transformations of the artworld divides the master narrative in three paradigmatic moments of the philosophical evolution of art’s history. The crucial stages in the narrative of the arts were the artistic Renaissance and its more than five centuries legacy (indebted to the representational canon of Raphael’s painting), the avant-gardes at the end of the 19th century and the beginning of the 20th century (suggestively exemplified by the art of Marcel Duchamp), and the arts of the second half of the 20th century (with Danto’s special focus on the American pop art and Andy Warhol). The present investigation considers the philosophical narrativism of late modernity only, starting with the incipient impressionist and post-impressionist ideological agendas in art. The last two stages best exemplify Danto’s philosophical narrativism in keeping with the American philosopher’s creed that – while the artistic program of the Renaissance and its artistic legacy in the first stage was internally committed to legitimizing the concept of accurate artistic representation – the agenda of the (above-mentioned) last two stages in the historical development of art was mostly ideological and external to the art itself. By and large, the present reassessment reflects on Danto’s most intimate belief that the historical evolution of the art in the last two stages unveils solid philosophical underpinnings.